Main Effects and Interaction Effects of Bank Ownership Types and Bank Core Capital Category to the Bank NPL Performance - Fongnawati Budhijono (International Journal of Business Studies, 2021)
Credit management capability is seen as a crucial aspect for banks sustainability. The variable that is directly related to bank credit risk is a non-performing loan (NPL) which is commonly used to assess the asset quality of a bank. The purpose of this research is to analyze main effects and interaction effects of bank ownership types and bank core capital category (BUKU) to the bank NPL performance. The study was conducted using secondary data obtained from bank quarterly reports from the Financial Services Authority (OJK) through the website ojk.go.id, bank financial reports, and infobank magazine. Bank’s performance in the classification of bank ownership types and bank core capital category were evaluated with respect to bank’s NPL which in this case is used as indicator of the bank’s performance. Tests were performed using TWO WAY ANOVA and Post Hoc Test. The findings of this study found that the main effect type of bank ownership had a significant effect on the performance of NPL management, the main effect of banks’ BUKU had no significant effect on the performance of NPL management and the interaction effect of bank type and banks’ BUKU had a significant effect on the performance of NPL management.